(untitled) - Wang, Shan Kuo (Boston, MA, 2000)
A broad range of disciplines--energy conservation and air quality issues, construction and design, and the manufacture of temperature-sensitive products and materials--is covered in this comprehensive handbook, Provide essential, up-to-date HVAC data, codes, standards, and guidelines, all conveniently located in one volume, A definitive reference source on the design, selection and operation of A/C and refrigeration systems
Keywords: Air conditioning,Refrigeration and refrigerating machinery